Analysis on the Change of Steam Turbine Back Pressure Under Operation of Low Pressure Economizer - Chuanling LIU; Minghui LIU; Zhenjiang CHEN; Ang SONG (发电技术, 2018)
After low pressure economizer was put into the unit, waste heat of boiler flue gas enters the regenerative system. The extraction steam returns to low pressure cylinder, and the steam volume increases, which causes the change of the back pressure of the steam turbine. According to the equivalent enthalpy drop theory, the calculation model of back pressure change was established. The model is verified through the test and analysis of one 220MW unit. Under 220MW working condition, the steam turbine back pressure is increased by 0.29 kPa. After the correction of the back pressure, the energy saving of "equivalent enthalpy drop method" decreases by 0.19%, which is closer to the energy saving of the "thermal test method". It shows that in the energy saving effect analysis of operating low-cost economizer with the "equivalent enthalpy drop method", the impact of back pressure changes on energy savings need to be considered.